PELATIHAN PEMANFAATAN INTERNET UNTUK MENUNJANG PELAKSANAAN TUGAS ADMINISTRASI PADA APARATUR DESA TEGALWERU KECAMATAN DAU KABUPATEN MALANG - Mohammad Maskan; Bambang Soepeno; Helmy Adisaksana; Siti Rohani (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Information technology grow up rapidly and its applied in the all of fields. One of field had applied information technology is office administration field, for the sample to fill personell data, selling, bussiness letter and so on. Officer of Tegalweru village, Dau District, Malang City in the administration manage in administrative in village’s administrative had used internet. For this, all of administrative officer that service to society have to know and apply internet. Unfortunetly, all of administrative officer of Tegalweru village, Dau District, Malang City not yet can operate to administrative based in internet. It is caused age have old years, their’s education level in their years not yet to teach of internet. Based on this cases, so need to training about internet applied to do administrative in the village office. The results shows that there is increasing to internet administrative science and it’s apllied It is caused by time of training all of trainees have antusiated, motivated and very open to change of administrative work system that will be done to service to society. For this, need to increasing their knowledge and about administrative base on internet with to do relationship about training about administrative based on iinternet training with Malang State Polytechnic in the future.